Comparison between Carbon-Peek volar locking plates and titanium volar locking plates in the treatment of distal radius fractures. (October 2017) - Perugia, Dario; Guzzini, Matteo; Mazza, Daniele; Iorio, Carlo; Civitenga, Carolina; Ferretti, Andrea
Abstract: Introduction: Unstable intra articular fractures of distal radius are frequently being managed with open reduction and internal fixation. Volar locking plate based on polyetheretherketon (PEEK) polymer has developed lately as an alternative to conventional metallic devices. The advantage of this kind of plates include the lack of metal allergies, radiolucency, low artefacts on MRI or imaging scans and the high resistance associated to loading forces. The aim of this study was to evaluate the clinical and radiological results using a new Carbon-PEEK volar locking plate compared with titanium volar locking plates for the treatment of distal radius fractures. Methods and Material: Thirty patients were included in this study. They all underwent traumatic intra-articular distal radius fractures and were surgically treated with volar locking plates. The patients were randomly divided in two groups: In Group A (15 patients) the fracture was stabilized with a CarboFix volar locking plate whereas in group B (15 patients) with an Acu-Lock Volar Distal Radius Plate. Range of motion (ROM), grip strength, Disabilities of the Arm, Shoulder and Hand (DASH) score and X-rays were evaluated. The mean follow up was 12 months. Results: Analysis of Wrist ROM revealed that there was no statistical significant difference ( p > 0.05) in regards to extension, flexion, ulnar deviation, radial deviation, supination and pronation comparing to the unaffected arm and between Group A and Group B. The mean score on the DASH was 15.3 in Group A and 13.2 in Group B ( p > 0.05). Patients were able to return to their normal activities of daily living at an average of 4 weeks post-op in both Groups. Overall, the mean VAS score was 3.6 There were no statistically significant differences ( p > 0.05) on X-Rays examination between two Groups in regards to alignment and fracture healing. Conclusions: Volar locking plates represent the most common procedure for the treatment of displaced distal radius fractures. In our series Carbon-peek volar locking plates seems to be analogue to titanium volar locking plates in terms of radiographic parameters and functional outcome.